Broadband Right-Handed Circular Polarized (RHCP) Antenna With Loop Metasurfaces - Abu Bakar, Hamzah; Abd Aziz, Mohamad Zoinol Abidin; Ahmad, Badrul Hisham; Ghani, Suhana; Hassan, Nornikman (Penerbit Universiti, UTeM, 2017)
-